Sex alteration in soft-shell clams ( Mya arenaria) in an intertidal zone of the Saint Lawrence River (Quebec, Canada) - Gagné, F; Blaise, C; Pellerin, J; Pelletier, E; Douville, M; Gauthier-Clerc, S; Viglino, L (Comparative biochemistry and physiology. Toxicology & pharmacology, 2003)
The purpose of this study was to verify whether any changes in sex ratio might occur in soft-shell clams ( Mya arenaria) located in an intertidal harbor zone located at the mouth of the Saguenay Fjord in the Saint Lawrence estuary (Baie Sainte-Catherine (BSC), Québec, Canada) likely to be contaminated by organotin compounds. Bivalves were harvested at the BSC harbor site and from two reference sites. Condition index (weight to length ratio), gonado-somatic index, sex ratio, vitellin-like proteins, organotin concentrations in gonad tissue, maturation stages of the gonads, the number of estradiol-17β binding sites and the capacity of female gonad extracts to produce estradiol-17β were determined in collected animals. Results showed that sex ratio in clams was significantly skewed toward males. Moreover, the condition and gonad-somatic indices, vitellin-like proteins in female gonads and the capacity of female gonads to produce estradiol-17β were significantly reduced at the harbor site with respect to the reference sites. Maturation status of male gonads was clearly delayed at the harbor site. Additionally, gonad tissue contained tributyltin (TBT) at an average level of 109±18 ngSn/g dry wt. at the harbor site while organotins were not detected from the reference sites. Finally, female gonads had a higher number of unoccupied estradiol binding sites at the harbor site indicating low levels of this steroid in this tissue. Overall, this paper is first to report that clams collected in the vicinity of a TBT contaminated harbor are subject to masculinizing effects which seems to be consistent with biological effects that organotins are known to exert toward some other marine invertebrates.